CONTINUOUS HORIZONTAL CASTING OF PIPE BRONZE BILLET - E. I. Marukovich; A. M. Branovitsky; J. A. Lebedinskij; V. A. Kharkov; Y. V. Sachenko (Литьë и металлургия)
An experimental and calculated thermal analysis of the continuous casting of bronze tube billets is developed. Calculated allowable thermal conditions of drawing for stable casting.